The ABC of Major Histocompatibility Complexes and T Cell Receptors in Health and Disease - Kedzierska, Katherine (Viral Immunol, 2020)
A seminal discovery of major histocompatibility complex (MHC) restriction in T cell recognition by Peter Doherty and Rolf Zinkernagel has led to 45 years of exciting research on the mechanisms governing peptide MHC (pMHC) recognition by T cell receptors (TCRs) and their importance in health and disease. T cells provide a significant level of protection against viral, bacterial, and parasitic infections, as well as tumors, hence, the generation of protective T cell responses is a primary goal for cell-mediated vaccines and immunotherapies. Understanding the mechanisms underlying generation of optimal high-avidity effector T cell responses, memory development, maintenance, and recall is of major importance for the rational design of preventative and therapeutic vaccines/immunotherapies. In this review, we summarize the lessons learned over the last four decades and outline our current understanding of the basis and consequences of pMHC/TCR interactions on T cell development and function, and TCR diversity and composition, driving better clinical outcomes and prevention of viral escape. We also discuss the current models of T cell memory formation and determinants of immunodominant T cell responses in animal models and humans. As TCR composition and diversity can affect both the protective capacity of T cells and protection against viral escape, defining the spectrum of TCR selection has implications for improving the functional efficacy of effector T cell responsiveness and memory formation.